Mitochondrial DNA enrichment reduced NUMT contamination in porcine NGS analyses. (14th June 2019) - Wang, Dan; Xiang, Hai; Ning, Chao; Liu, Hao; Liu, Jian-Feng; Zhao, Xingbo
Abstract: Genetic associations between mitochondrial DNA (mtDNA) and economic traits have been widely reported for pigs, which indicate the importance of mtDNA. However, studies on mtDNA heteroplasmy in pigs are rare. Next generation sequencing (NGS) methodologies have emerged as a promising genomic approach for detection of mitochondrial heteroplasmy. Due to the short reads, flexible bioinformatic analyses and the contamination of nuclear mitochondrial sequences (NUMTs), NGS was expected to increase false-positive detection of heteroplasmy. In this study, Sanger sequencing was performed as a gold standard to detect heteroplasmy with a detection sensitivity of 5% in pigs and then one whole-genome sequencing method (WGS) and two mtDNA enrichment sequencing methods (Capture and LongPCR) were carried out. The aim of this study was to determine whether mitochondrial heteroplasmy identification from NGS data was affected by NUMTs. We find that WGS generated more false intra-individual polymorphisms and less mapping specificity than the two enrichment sequencing methods, suggesting NUMTs indeed led to false-positive mitochondrial heteroplasmies from NGS data. In addition, to accurately detect mitochondrial diversity, three commonly used tools—SAMtools, VarScan and GATK—with different parameter values were compared. VarScan achieved the best specificity and sensitivity when considering the base alignment quality re-computation and the minimum variant frequency of 0.25. It also suggested bioinformatic workflow interfere in the identification of mtDNA SNPs. In conclusion, intra-individual polymorphism in pig mitochondria from NGS data was confused with NUMTs, and mtDNA-specific enrichment is essential before high-throughput sequencing in the detection of mitochondrial genome sequences.